2005
DOI: 10.1111/j.1600-0749.2005.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of piperlonguminine on melanin production in melanoma B16 cell line by downregulation of tyrosinase expression

Abstract: Tyrosinase is a key enzyme for melanin biosynthesis, and hyperpigmentation disorders are associated with abnormal accumulation of melanin pigments, which can be improved by treatment with depigmenting agents. In the present study, piperlonguminine from Piper longum was discovered to inhibit melanin production in melanoma B16 cells stimulated with alpha-melanocyte stimulating hormone (alpha-MSH), 3-isobutyl-1-methylxanthine or protoporphyrin IX, where the compound exhibited stronger depigmenting efficacy than k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 41 publications
4
71
0
Order By: Relevance
“…38) A recent report has shown that piperlonguminine decreased CREB phosphorylation and MITF production in a dose-dependent manner in -MSHstimulated B16 melanoma cells, which resulted in reduced tyrosinase and melanin levels. 39) In accordance with these findings, our results indicate that CEFV also inhibits CREB phosphorylation and MITF expression in -MSH-stimulated B16 melanoma cells. Previous studies have suggested that the ERK signaling pathway is involved in the regulation of melanogenesis.…”
Section: Discussionsupporting
confidence: 81%
“…38) A recent report has shown that piperlonguminine decreased CREB phosphorylation and MITF production in a dose-dependent manner in -MSHstimulated B16 melanoma cells, which resulted in reduced tyrosinase and melanin levels. 39) In accordance with these findings, our results indicate that CEFV also inhibits CREB phosphorylation and MITF expression in -MSH-stimulated B16 melanoma cells. Previous studies have suggested that the ERK signaling pathway is involved in the regulation of melanogenesis.…”
Section: Discussionsupporting
confidence: 81%
“…Piperlongumine has multiple pharmacologic activities: it has been described as a platelet aggregation inhibitor (3), an anxiolytic agent (4), an antidepressant (5), an antinociceptive agent (6), an anti-atherosclerotic agent (7), an antidiabetic agent (8), an anti-inflammatory agent (9), and an infectious pathogen inhibitor (10). Furthermore, piperlongumine has been reported to kill multiple types of cancer cells, inhibit metastasis, and have antitumor activities in a variety of animal models (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…The melanin inhibition effect of compound [1] was not due to cytotoxicity, because the melanin assay was performed by adjusting the number of cells and the inhibition of cell growth was observed at the concentration of 0.25 mg/ml (0.53 mM). Several other melanin biosynthesis inhibitors that do not inhibit tyrosinase activity have been isolated from plants; these include 4,5-dihydroxy-3-propenyl-2-cyclopenten-1-one (terrein; IC 50 Լ30 mM) from Penicillium species, 21) piperlonguminine (IC 50 Լ10 mM) from Piper longum (Piperaceae), 12) and coumarin compounds such as soimperatorin and imperatorin (IC 50 Ͼ100 mM) from Angelica dahurica. 22) Thus, compound [1] is one of the most potent melanin Total RNA was extracted from cells were cultured for 1 d in medium containing 0.125 mg/ml of 3b,16b-dihydroxy-21a-hydroperoxy-20(30)-taraxastene [1].…”
Section: Discussionmentioning
confidence: 99%
“…These compounds inhibit the formation of melanin pigment by inhibiting the activity of tyrosinase, which is a key enzyme in melanin biosynthesis. Other tyrosinase inhibitors have been isolated from Morus alba L. (Moraceae), 9) Machilus thunbergii (Lauraceae), 10) Trichosanthes kirilowii (Cucurbitaceae), 11) Piper longum (Piperaceae) 12) and Artocarpus heterophyllus (Moraceae). 13) On the other hand, linoleic acid, which is formed as a secondary metabolite in various plants, inhibits the formation of melanin pigment without inhibiting tyrosinase activity.…”
mentioning
confidence: 99%